2015
DOI: 10.2214/ajr.14.13630
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Diagnostic Reference Levels for Pediatric Peripheral and Abdominal Fluoroscopically Guided Procedures

Abstract: Estimates of dose indexes of pediatric peripheral and abdominal fluoroscopically guided, clinical procedures should assist in the development of DRLs to foster management of radiation doses of pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…If the median P KA and/or K a,r in a particular institution exceeds the corresponding DRL value, evaluation of fluoroscopy time and the number of acquired images may help to determine whether these are contributing factors. The Commission recommends that data for all suitable DRL quantities that are available should be tracked for interventional procedures at facilities where these procedures are performed. (191) While the literature contains data for K a,r , P KA , or fluoroscopy time at multiple healthcare facilities and nations for adult interventional fluoroscopic procedures, these data have only been published recently for paediatric examinations, and the numbers of cases in these paediatric studies are typically more limited (Strauss et al., 2015; Ubeda et al., 2015). (192) If the median values of the DRL quantities are higher than expected, investigation of the fluoroscopic equipment is appropriate.…”
Section: Interventional Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…If the median P KA and/or K a,r in a particular institution exceeds the corresponding DRL value, evaluation of fluoroscopy time and the number of acquired images may help to determine whether these are contributing factors. The Commission recommends that data for all suitable DRL quantities that are available should be tracked for interventional procedures at facilities where these procedures are performed. (191) While the literature contains data for K a,r , P KA , or fluoroscopy time at multiple healthcare facilities and nations for adult interventional fluoroscopic procedures, these data have only been published recently for paediatric examinations, and the numbers of cases in these paediatric studies are typically more limited (Strauss et al., 2015; Ubeda et al., 2015). (192) If the median values of the DRL quantities are higher than expected, investigation of the fluoroscopic equipment is appropriate.…”
Section: Interventional Proceduresmentioning
confidence: 99%
“…(191) While the literature contains data for K a,r , P KA , or fluoroscopy time at multiple healthcare facilities and nations for adult interventional fluoroscopic procedures, these data have only been published recently for paediatric examinations, and the numbers of cases in these paediatric studies are typically more limited (Strauss et al., 2015; Ubeda et al., 2015).…”
Section: Interventional Proceduresmentioning
confidence: 99%
“…A few studies in the United States of pediatric patient dose levels during fluoroscopy from singe institutions have been published. [18][19][20][21][22] While dose data as a function of patient thickness are limited, two comparisons can be made. A publication in 2008 found that for 21 patients 10-14 cm in thickness received an average RAK of 0.58 mGy with a (0.28-0.80) 95% confidence interval for a VCUG examination.…”
Section: Discussionmentioning
confidence: 99%
“…La ICRP introdujo en 1996 los niveles de referencia para dignóstico (DRL) (10,11) que desde entonces se usan para optimizar y monitorizar los niveles de radiación a los que se exponen los pacientes. Este concepto es fundamental y ha sido revisado por múltiples instituciones internacionales (11)(12)(13)(14)(15)(16). Dichos valores ayudan a orientar si la dosis de radiación del paciente es inusualmente alta.…”
Section: Introductionunclassified